Synthesis and Characterization of 2-(Hydroxyimino)-1-(phenylpropylidene)thiocarbonohydrazide and its Metal Complexes with Co(II), Ni(II) and Cu(II) Ions - A. Venkatchallam; R. G. Deshmukh; Dilip C. Sawant (E-Journal of Chemistry)
Synthesis and characterization of 2-(hydroxyimino)-1-(phenyl propylidene) thiocarbonohydrazide (called ‘HPTCHOPD’) was studied. The synthesized compound having the molecular formula C10H13N5OS, where in isonitrosopropiophenone is reacted with thiocarbonohydrazide in presence of sodium acetate in ethanol-water mixture. The yield which is comprises effecting the reaction in the presence of sodium acetate. Also the present work report a process for producing metal complexes having the formula ML2 and (ML)2 Cl, wherein M is the divalent metal cation, like cobalt (Co+2), nickel (Ni+2) and copper (Cu+2). The compound HPTCHOPD is admixed with a basic divalent compound that is halide, mainly chloride of Co+2, Ni+2 and Cu+2 in presence of methanol-water mixture. The metal complexes so produced are characterized on the basis of spectral, elemental and magnetic analysis; reveal interesting geometries and bonding features. The data suggested square planar geometry for Co+2 complex, a distorted tetrahedral/square planar-octahedral geometry for Ni+2 complex and a bridged structure for Cu+2 complex.